Tuesday

July 29, 2014

July 29, 2014

Posted by **Yolie** on Thursday, February 2, 2012 at 1:53am.

-5e^-x + 9 = 6

I subtracted 9 to both sides and got:

-5e^-x= -3 < this is where I'm stuck at.

- Alg2 -
**Anonymous**, Thursday, February 2, 2012 at 2:12am- 5e ^ ( - x ) + 9 = 6

- 5e ^ ( - x ) = 6 - 9

- 5e ^ ( - x ) = - 3 Divide both sides by - 5

e ^ ( - x ) = 3 / 5

Take the natural logarithm of both sides:

- x = - log (5 / 3 )

Divide both sides by -1:

x = log ( 5 / 3 )

x = 0.510826

Remark:

log mean natural logarithm

- Alg2 -
**Yolie**, Thursday, February 2, 2012 at 2:23amTysm :D

**Related Questions**

Math - Graph the equation. Be sure to simplify equation before graphing it. -18+...

science - rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i ...

MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...

math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...

algebra - solve each literal equation for the indicated variable linear equation...

Algebra - I have some problems that I am having trouble with and I have some ...

Pre Cal - 6-x=2x+9 If you are to solve the equation for x, first try to get the ...

math - How would I use separation of variables to solve the initial value ...